Aspects and Dilemmas of Euthanasia in Modern Times - Greš, Alen; Staver, Dijana; Radovančević, Ljubomir (Scripta Medica, 2024)
Euthanasia is a very complex medical and moral issue. The name has taken throughout history quite different meanings especially in recent decades. There have been many controversial debates and ethical questions raised in modern society. The aim of the paper was to introduce in more detail the issue of euthanasia in the modern world and to review the decisions on this issue. The end of life is still a part of life. It is of great importance for every person and requires true compassion and solidarity. The task is to restore human dignity, by respecting the will of the sedating patient. It is the responsibility of doctors and medical staff to use their comprehensive knowledge and ethical approach to provide calm patients with peace and tranquillity. Euthanasia is a discipline. It is also a concept and a term full of conflicts, which need to be analysed. Therefore, it is necessary to consider the criteria of the bioethical aspect of this activity. The right to euthanasia is not ethically indifferent. We can expect in the near future a deeper understanding of the euthanasia issue.
Keywords: Euthanasia; Modern society; End of life; Human dignity; Jurisprudence